Política de saúde mental no Brasil: impactos da implementação dos Centros de Atenção Psicossocial (CAPS) sobre internações e mortalidade feminina - Carvalho, Gabriel Diego de (Universidade Estadual de Ponta Grossa (UEPG), 2026)
Mental health policy in Brazil has as one of its central pillars the replacement of the hospital centered model with a community-based care network, in which Psychosocial Care Centers (CAPS) play a strategic role in the organization of care and in the reduction of psychiatric hospitalizations. In this context, the expansion of CAPS throughout the national territory constitutes one of the main initiatives of the National Mental Health Policy, with expected impacts on the use of hospital services, especially among more vulnerable populations. Thus, the objective of this dissertation is to evaluate the impact of the implementation of Psychosocial Care Centers on hospitalization rates and mortality due to mental and behavioral disorders among women aged 18 years or older in Brazilian municipalities over the period from 2008 to 2019. Additionally, this study seeks to understand how socioeconomic heterogeneity across municipalities shapes the effects of the policy, with an emphasis on municipalities characterized by greater economic vulnerability. To this end, municipal-level administrative panel data from the Hospital Information System of the Brazilian Unified Health System (SIH/SUS) are used, combined with information on CAPS implementation and socioeconomic indicators. The empirical strategy is based on a Difference-in-Differences model with staggered treatment adoption, incorporating dynamic effects estimated through an event study approach, which allows the exploration of temporal and spatial variation in the implementation of CAPS. The results indicate that, when considering the full set of Brazilian municipalities, no statistically significant effects of CAPS presence are observed on female hospitalizations due to mental and behavioral disorders. However, when the analysis is restricted to municipalities characterized by greater socioeconomic vulnerability, there is evidence of consistent, albeit gradual, dynamic effects associated with CAPS implementation, suggesting a progressive reduction in female hospitalizations over time. These results point to relevant heterogeneity in policy impacts, indicating that the effects of CAPS are more pronounced in contexts with greater dependence on the public health system. In contrast, no statistically significant impacts are identified on female mortality due to mental and behavioral disorders, indicating that the action of CAPS primarily affects the organization of care and patterns of mental health service utilization, without directly translating into final outcomes such as death.
Keywords: Centro de Atenção Psicossocial; Política Nacional de Saúde Mental; internações; mulheres; Diferenças-em-Diferenças